Volleyball Learning Model Based On Teaching Games For Understanding (TGFU) Junior High School Category - Samsudin, Samsudin (STKIP Muhammadiyah Kuningan, 2024)
The purpose of this study was to develop a volleyball learning model based on teaching games for understanding (TGFU) for Junior High School Student in SMPN 13 Bekasi City. The research method uses research and development methods adopted from the theory of Borg & Gall. The research subjects in the volleyball passing learning model are upper grade Junior High School students. There are ten steps used in this research, namely needs analysis, initial product creation, expert evaluation, small group trial, product revision, large group trial, product revision, effectiveness test, revision, and final product. The results of the expert validation of Physical Education and Sports learning for the bottom pass of 77.08%, the upper pass of 81.25% so that the is valid. The results of the expert validation of volleyball games were obtained for the lower pass of 79.17% and the upper pass of 83.33% so that it was suitable and easy to use. improve volleyball passing skills worth using. The results of the small group trial obtained 80.73% indicating a good category, the large group trial results were 81.10% with good classification, and the results of the effectiveness test obtained a post-test mean difference test in the control group and the experimental group obtained t0 of 3.386 and t table 1.671 with 60 degrees of freedom and = 0.05. Thus, t0 = 3.386 > ttable = 1.671 or H0 is rejected. The implication of this research is that the volleyball learning model is feasible and effective for use by upper grade Junior High School students.